2014
DOI: 10.1158/1538-7445.am2014-2860
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2860: miR-21 overexpression assessed by in situ hybridisation is an independent predictor of survival in patients with resected pancreatic ductal adenocarcinoma

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) has a 5-year survival of only 3%. Surgery is the only curative option but only 15-20% of patients are suitable and post-operative recovery is long, with significant early mortality and a 5-year survival of around 20%. Thus not all patients benefit from surgery and prognostication and subsequent stratification of patients to surgical or non-surgical management could be better. Initial staging currently relies on imaging; the main pathological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…who found consistently reduced let-7 expression levels in lung cancer patients significantly associated with worse survival outcomes post-tumour resection [ 147 , 148 ]. Following this, a large clinical study involving a total of 686 patients, showed that high miR-21 expression in PDAC tumours was significantly correlated with shorter overall survival, along with other clinical features of advanced development, such as high tumour grade and presence of lymph node metastasis [ 149 ]. However, those patients with high miR-21 expression are also predicted to have an increased survival benefit after receiving gemcitabine-based adjuvant chemotherapy as compared to low miR-21 patients.…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers For Pancreati...mentioning
confidence: 99%
“…who found consistently reduced let-7 expression levels in lung cancer patients significantly associated with worse survival outcomes post-tumour resection [ 147 , 148 ]. Following this, a large clinical study involving a total of 686 patients, showed that high miR-21 expression in PDAC tumours was significantly correlated with shorter overall survival, along with other clinical features of advanced development, such as high tumour grade and presence of lymph node metastasis [ 149 ]. However, those patients with high miR-21 expression are also predicted to have an increased survival benefit after receiving gemcitabine-based adjuvant chemotherapy as compared to low miR-21 patients.…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers For Pancreati...mentioning
confidence: 99%
“…In addition to making the diagnosis, the level of miR-21 can reflect treatment efficacy in pancreatic cancer [ 120 ]. Patients with lower miR-21 expression after treatment have been found to have a longer median survival period compared to those with persistently high expression [ 121 ]. The diagnostic potential, prognostic value, and implications for therapeutic strategies indicate that the foundation of miR-21 in PDAC will continue to be a pivotal area of research, shaping both diagnostic and therapeutic paradigms in managing pancreatic ductal adenocarcinoma…”
Section: Clinical Implications and Importance Of Mir-21 In Pancreatic...mentioning
confidence: 99%
“…Several retrospective studies have investigated the importance of miR-21 as a prognostic biomarker. The results have shown that high levels of miR-21 expression are associated with significantly decreased overall survival and disease-free survival in PDAC patients [ 121 , 130 ]. For instance, in the study of 76 patients diagnosed with pancreatic cancer, Ali S. et al identified that increased miR-21 was significantly associated with worse survival and chemotherapy resistance [ 131 ].…”
Section: Clinical Implications and Importance Of Mir-21 In Pancreatic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue expression of miR-21 was evaluated by chromogenic in situ hybridization (CISH). By applying this method to tissue microarrays of well-annotated PDAC cohorts of patients, the researchers showed that the epithelial expression of miR-21 is an independent robust prognostic biomarker in PDAC, prompting prospective trials for further validation and application in the clinical setting [ 56 ]. The above-mentioned studies also showed that PDAC cells treated with gemcitabine and transfected with pre-miR-21 became less sensitive and had a decreased apoptosis induction, while transfection with anti-miR-21 enhanced the gemcitabine sensitivity.…”
Section: Introductionmentioning
confidence: 99%